EFFECT OF TAPING AND CLOSED KINETIC CHAIN VERSUS TRADITIONAL APPROACH IN OSTEOARTHRITIS KNEE - P.SUDHESH (International Journal of Pharma and Bio Sciences, 2013)
Osteoarthritis of the knee major cause of pain and disability. There is no specific treatment to modify the disease. There are various etiological factors for Osteoarthritis Knee of which highlighted factor biomechanical alteration and quadriceps weakness, the advancement treatment of Osteoarthritis Knee treatment shows biomechanical alteration can reduce the severity. Here the biomechanical factor is considered to be increased lateral vector force to be major source of severity for this medial tapping and close kinetic chain exercise said to reduce the severity. Hence the aim of study to compare the effect of tapping and closed kinetic chain with traditional approach in the management of osteoarthritis knee. For this 30 patients were selected an randomly divided into two group experimental and control group both group were assessed pre and post by WOMAC SCALE and ‘ Q’ ANGLE. After that experimental group tapping and close kinetic exercise were given. Finally result were tabulated. From the result experimental group show significant improvement than control group. Hence it is concluded that taping and closed kinetic chain exercise has satisfactory effectiveness in management of osteoarthritis knee compared to traditional and therapeutic approach